SYSTEMATIC REVIEW OF DENGUE VACCINE EFFICACY - Al Ansoriani, Marogi; Rahayu Kosasih, Dina Mentayani; Alam Al Ansoriani, Nuansa Nur Alam Al Ansoriani (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Dengue fever belongs to the arboviruses which are the genus Flavivirus (family Flaviridae) and is transmitted through female mosquitoes that carry the dengue virus. There are four serotypes of dengue fever, namely DENV1, DENV2, DENV3, and DENV4. The number of cases of dengue fever infection is estimated at 390 million spread across 128 countries. Although globally, only 3.2 million cases were reported to WHO in 2015. There are many challenges in developing a safe and effective dengue fever vaccine. Infection with one of the four dengue virus serotypes has been shown to provide long-term protection against homotypic reinfection, but protection against secondary heterotypic infection is only temporary. The aim: This study aims to show about dengue vaccine efficacy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 83 articles, whereas the results of our search on SagePub brought up 147 articles. The results of the search conducted for the last year of 2013 yielded a total 79 articles for PubMed and 90 articles for SagePub. The result from title screening, a total 31 articles for PubMed and 24 articles for SagePub. In the end, we compiled a total of 7 papers. We included five research that met the criteria. Conclusion: Dengue vaccines can be produced with live attenuated chimeric recombinant viruses, live attenuated viruses, inactivated viruses, recombinant proteins and mRNA vaccines. Each of these vaccines has good efficacy in terms of protection against dengue virus.